High-speed low-temperature bearing grease and preparation method thereof

By using homemade fluoropolyurea structural thickener and nano-ferrous tetraoxide/ZIF-67 coated structure in high-speed and low-temperature bearing grease, the problems of high viscosity and insufficient water resistance of grease under high-speed and low-temperature conditions are solved, and better lubricating effect and flame retardant performance are achieved.

CN116987541BActive Publication Date: 2025-04-22安徽和欣润滑科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310972611.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-03
Publication Date
2025-04-22
Estimated Expiration
2043-08-03

AI Technical Summary

Technical Problem

The existing high-speed low-temperature bearing grease has a high viscosity under high-speed low-temperature conditions, which is prone to extrusion or formation of precipitates, affecting the lubrication effect. At the same time, the water resistance of aluminum-based grease is insufficient.

Method used

The homemade fluoropolyurea structure thickener is used to synthesize 1,4-bis(2-trifluoromethyl-4-aminophenoxy)benzene to increase the viscosity and shear resistance of the grease, and flame retardant magnetic particles are prepared by nano-ferrous tetraoxide and ZIF-67 coated structure to improve the water resistance and flame retardant properties of the grease.

Benefits of technology

It effectively avoids precipitation of thickener, improves the water resistance and corrosion resistance of the grease, and enhances its flame retardant performance, and is suitable for high-speed and low-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004376065020000101
    Figure BDA0004376065020000101
Patent Text Reader

Abstract

The invention discloses a high-speed low-temperature bearing grease and a preparation method thereof, belonging to the technical field of grease. The grease comprises a base oil, a thickener, flame-retardant magnetic particles, a tackifier, a structural stabilizer and an antioxidant. Compared with a conventional distearate hydroxyaluminum thickener, the self-made thickener does not produce precipitation and has better water resistance. The volume of the trifluoromethyl side group is large, which can increase the distance between molecules, hinder the aggregation of fillers such as magnetic flame-retardant particles in the grease, and avoid precipitation formation. The magnetic flame-retardant particles increase their dispersibility and stability through the action of a magnetic field, and reduce the influence of external water scouring. After the hexachlorocyclotriphosphazene and 4,4'-diaminodiphenyl ether react, they are coated on the surface of ZIF-67 coated ferroferric oxide particles. The ZIF-67 coated ferroferric oxide particles have a higher porosity, which helps to increase the bonding strength of the flame retardant substance and increase the flame retardant performance of the high-speed low-temperature bearing grease.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lubricating grease, and in particular relates to high-speed and low-temperature bearing lubricating grease and a preparation method thereof. Background Art

[0002] Bearings are an important component in mechanical equipment. Their main function is to support the mechanical rotating body, reduce the friction coefficient during its movement, and ensure its rotation accuracy. Mechanical equipment will inevitably be affected by the external environment during operation, causing parts to rust or damage, and bearings are also susceptible to corrosion, or dust and other impurities entering, causing increased wear. Therefore, in order to increase the service life of the bearing, a lubrication system is required for protection.

[0003] The lubrication system of a bearing generally includes lubricating oil and lubricating grease. Lubricating oil can protect bearings from rust and corrosion, but lubricating oil has high fluidity and is easy to evaporate. Grease is a paste-like lubricating material composed of base oil, thickener, additives and filler. It has low fluidity and is not prone to leakage. It can simplify the peripheral structure of the bearing and form a lubricating film on the friction surface of the bearing, reducing friction and wear. It can also prevent the bearing from corrosion and oxidation.

[0004] High-speed and low-temperature bearing grease is mainly used for bearings in high-speed and low-temperature working environments, such as wind turbines, aerospace equipment, and refrigeration equipment. The grease needs to withstand the challenge of high-speed rotation in a very cold environment. For example, wind turbines are installed in the open outdoors, where the environment is relatively harsh. During use, water vapor may enter the bearings, causing the grease to emulsify and lose its lubrication effect. Commonly used water-resistant greases include aluminum-based greases, which are added with aluminum soap during the preparation process. However, the water resistance of aluminum-based greases is still average, and the viscosity is high under high-speed and low-temperature conditions, which makes it easy to extrude or form sediment, affecting the lubrication effect. Summary of the invention

[0005] One of the purposes of the present invention is to provide a high-speed and low-temperature bearing grease, which increases the water resistance of the grease by a homemade thickener to solve the problem that aluminum soap is easily precipitated in the grease; the second purpose is to provide a method for preparing a high-speed and low-temperature bearing grease.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] High-speed low-temperature bearing grease comprises the following raw materials in parts by mass:

[0008] Base oil 75-85 parts, thickener 12-18 parts, flame retardant magnetic particles 8-12 parts, tackifier 1-2.5 parts, structural stabilizer 0.5-2 parts, antioxidant 0.5-1 parts;

[0009] Furthermore, the base oil is a poly-alpha-olefin having a number average molecular weight of 2000-4000.

[0010] Furthermore, the tackifier is polyisobutylene with a number average molecular weight of 1500-2000.

[0011] Furthermore, the structural stabilizer is any one of sodium stearate, calcium stearate and zinc stearate.

[0012] Furthermore, the antioxidant is any one of 2,6-di-tert-butyl-4-methylphenol and 2,6-di-tert-butyl-p-cresol.

[0013] Further, the thickener is prepared by the following steps:

[0014] Step 1: Mix choline chloride and urea in a mass ratio of 1:1, stir for 40-60 minutes at 120-125°C and 200-500r / min, and cool to obtain an ionic liquid; add the ionic liquid into a reactor, then add 2-chloro-5-nitrotrifluorotoluene and hydroquinone into the reactor, stir and react for 3-4 hours at 80-90°C, stir and mix the reaction product with the same mass of deionized water, then add ethyl acetate with an equal volume to the deionized water and stir for 20-30 minutes, stand and extract, collect the organic phase and then remove the ethyl acetate by rotary evaporation, recrystallize with anhydrous ethanol, complete the product purification, and obtain 1,4-bis(2-trifluoromethyl-4-nitrophenoxy)benzene.

[0015] Step 2: Add 1,4-bis(2-trifluoromethyl-4-nitrophenoxy)benzene and anhydrous ethanol into a reactor, add Raney nickel as a catalyst under nitrogen protection, then introduce hydrogen to stabilize the pressure of the reactor at 4-4.2 MPa, carry out reduction reaction at 60-65° C. for 3-3.5 hours, filter, stir and mix the reaction solution with 2 times the mass of deionized water, filter again after solid is precipitated, and dry the solid to obtain 1,4-bis(2-trifluoromethyl-4-aminophenoxy)benzene.

[0016] Step 3: Add 1,4-bis(2-trifluoromethyl-4-aminophenoxy)benzene to the reaction kettle, then add acetone as a solvent and stir for 20-30 minutes, add toluene diisocyanate, stir and react at 55-70°C for 30-40 minutes, filter, wash the filter cake with deionized water for 3-5 times, vacuum dry at 40-50°C, crush, and pass through a 200-mesh sieve to obtain a fluorinated polyurea thickener.

[0017] Furthermore, the usage ratio of the ionic liquid, 2-chloro-5-nitrotrifluorotoluene and hydroquinone is 2.8-3 g:45 g:11 g.

[0018] Furthermore, the usage ratio of 1,4-bis(2-trifluoromethyl-4-nitrophenoxy)benzene, anhydrous ethanol and Raney nickel is 2.4-2.5 g:20 g:0.14-0.15 g.

[0019] Furthermore, the usage ratio of 1,4-bis(2-trifluoromethyl-4-aminophenoxy)benzene, acetone and toluene diisocyanate is 17.4g:150-160g:42.8g.

[0020] Furthermore, the flame retardant magnetic particles are prepared by the following steps:

[0021] Step 1: Add cobalt nitrate hexahydrate, 2-methylimidazole, deionized water and N,N-dimethylformamide into a reactor, stir at 40-60°C for 20-30 minutes and ultrasonically treat for 10-15 minutes, then add nano-ferroferric oxide into the reactor, stir and react at 60-65°C for 2-3 hours, cool, centrifuge, wash the precipitate with anhydrous ethanol for 3-5 times, and dry to obtain ZIF-67 coated ferroferric oxide particles.

[0022] Step 2: Disperse the ZIF-67-coated ferrosoferric oxide particles and hexachlorocyclotriphosphazene with 1,4-dioxane and add them into the reactor, then add 4,4'-diaminodiphenyl ether, stir at 80-85°C for 20-24h, cool, centrifuge, wash the precipitate with anhydrous ethanol for 3-5 times, and dry to obtain flame-retardant magnetic particles.

[0023] Furthermore, the usage ratio of cobalt nitrate hexahydrate, 2-methylimidazole, deionized water, N,N-dimethylformamide and nano-ferrosoferric oxide is 0.4-0.5g: 10-12g: 50-60mL: 270-300mL: 3-3.5g.

[0024] Furthermore, the dosage ratio of ZIF-67 coated ferrosoferric oxide particles, hexachlorocyclotriphosphazene, 1,4-dioxane and 4,4'-diaminodiphenyl ether is 0.5-0.6 g: 2.5-3 g: 100-120 mL: 2.5-3 g.

[0025] The preparation method of high-speed low-temperature bearing grease comprises the following steps:

[0026] Add the base oil into the reactor, add the thickener into the reactor at 60-80℃ and a stirring speed of 200-500r / min, continue stirring for 30-40min after the thickener is added, then heat up to 160-180℃, add the tackifier, structural stabilizer and antioxidant and stir for 30-40min, cool down to 80-100℃, add flame-retardant magnetic particles and continue stirring for 20-30min, cool to obtain high-speed and low-temperature bearing grease.

[0027] Beneficial effects of the present invention:

[0028] The high-speed and low-temperature bearing grease of the present invention is added with a self-made polyurea structure thickener, and compared with the conventional distearate hydroxyaluminum thickener, it does not produce precipitation and has better water resistance; in the process of preparing the thickener, 1,4-bis(2-trifluoromethyl-4-aminophenoxy)benzene is synthesized to introduce benzene rings, ether bonds and trifluoromethyl groups therein, a large number of benzene ring structures help to increase the viscosity and shear resistance of the grease, the ether bonds increase the flexibility of the thickener, and help to increase the anti-wear performance, the trifluoromethyl group is oleophobic and hydrophobic, and is easily dispersed in the base oil, the trifluoromethyl side group has a large volume, can increase the distance between molecules, hinder the aggregation of fillers such as magnetic flame retardant particles in the grease, avoid precipitation formation, and can increase the water resistance and corrosion resistance of the grease.

[0029] The magnetic flame retardant particles use nano-ferroferric oxide as a skeleton, and the magnetic field increases its dispersibility and stability, reducing the impact of external moisture erosion; the nano-ferroferric oxide is wrapped by ZIF-67 with a zeolite imidazole framework structure formed by the coordination of cobalt ions and 2-methylimidazole, and hexachlorocyclotriphosphazene and 4,4'-diaminodiphenyl ether are reacted and coated on the surface of the ZIF-67 coated ferroferric oxide particles. The ZIF-67 coated ferroferric oxide particles have a higher porosity, which helps to increase the binding strength of the flame retardant. Finally, the stably dispersed magnetic flame retardant particles help to increase the flame retardant properties of high-speed and low-temperature bearing grease. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Example 1

[0032] This embodiment provides a high-speed low-temperature bearing grease, including the following implementation steps:

[0033] Step 1: Mix choline chloride and urea in a mass ratio of 1:1, stir for 40 minutes at 120°C and 200 r / min, and cool to obtain an ionic liquid; add 5.6 kg of ionic liquid into a reactor, then add 90 kg of 2-chloro-5-nitrotrifluorotoluene and 22 kg of hydroquinone into the reactor, stir and react for 3 hours at 80°C, stir and mix the reaction product with the same mass of deionized water, add ethyl acetate in an equal volume to the deionized water, stir for 20 minutes, stand and extract, collect the organic phase, and then remove the ethyl acetate by rotary evaporation, and recrystallize with anhydrous ethanol to purify the product to obtain 1,4-bis(2-trifluoromethyl-4-nitrophenoxy)benzene.

[0034] Step 2: Add 24 kg of 1,4-bis(2-trifluoromethyl-4-nitrophenoxy)benzene and 200 kg of anhydrous ethanol into a reactor, add 1.4 kg of Raney nickel as a catalyst under nitrogen protection, then introduce hydrogen to discharge nitrogen and stabilize the pressure of the reactor at 4 MPa, perform a reduction reaction at 60° C. for 3 h, filter, stir and mix the reaction solution with 2 times the mass of deionized water, filter again after solid precipitates, and dry the solid to obtain 1,4-bis(2-trifluoromethyl-4-aminophenoxy)benzene.

[0035] Step 3: Add 20.88 kg of 1,4-bis(2-trifluoromethyl-4-aminophenoxy)benzene to the reactor, then add 180 kg of acetone as a solvent and stir for 20 minutes, add 51.36 kg of toluene diisocyanate, stir and react at 55°C for 30 minutes, filter, wash the filter cake with deionized water 3 times, vacuum dry at 40°C, crush, and pass through a 200-mesh sieve to obtain a fluorinated polyurea thickener.

[0036] Step 4: Add 4 kg of cobalt nitrate hexahydrate, 100 kg of 2-methylimidazole, 500 L of deionized water and 2700 L of N,N-dimethylformamide into the reactor, stir at 40 ° C for 20 min and ultrasonically treat for 10 min, then add 30 kg of nano-iron tetroxide into the reactor, stir and react at 60 ° C for 2 h, cool, centrifuge, wash the precipitate with anhydrous ethanol 3 times, and dry to obtain ZIF-67 coated iron tetroxide particles.

[0037] Step 5: Disperse 15 kg of ZIF-67-coated ferrosoferric oxide particles and 75 kg of hexachlorocyclotriphosphazene with 3000 L of 1,4-dioxane and add them into the reactor. Then add 75 kg of 4,4'-diaminodiphenyl ether, stir at 80°C for 20 hours, cool, centrifuge, wash the precipitate with anhydrous ethanol for 3 times, and dry to obtain flame-retardant magnetic particles.

[0038] Step six: add 75kg of poly-α-olefin with a number average molecular weight of 2000 into the reactor, add 12kg of thickener into the reactor at 60°C and a stirring speed of 200r / min, continue stirring for 30min after the thickener is added, then heat up to 160°C, add 1kg of polyisobutylene with a number average molecular weight of 1500, 0.5kg of sodium stearate and 0.5kg of 2,6-di-tert-butyl-4-methylphenol and stir for 30min, cool to 80°C, add flame-retardant magnetic particles and continue stirring for 20min, cool to obtain high-speed and low-temperature bearing grease.

[0039] Example 2

[0040] This embodiment provides a high-speed low-temperature bearing grease, including the following implementation steps:

[0041] Step 1: Mix choline chloride and urea in a mass ratio of 1:1, stir for 50 minutes at 122°C and 350r / min, and cool to obtain an ionic liquid; add 5.8kg of ionic liquid into a reactor, then add 90kg of 2-chloro-5-nitrotrifluorotoluene and 22kg of hydroquinone into the reactor, stir and react at 85°C for 3.5h, stir and mix the reaction product with the same mass of deionized water, add ethyl acetate in an equal volume to the deionized water, stir for 25min, stand and extract, collect the organic phase, and then remove the ethyl acetate by rotary evaporation, and recrystallize with anhydrous ethanol to purify the product to obtain 1,4-bis(2-trifluoromethyl-4-nitrophenoxy)benzene.

[0042] Step 2: Add 24.5 kg of 1,4-bis(2-trifluoromethyl-4-nitrophenoxy)benzene and 200 kg of anhydrous ethanol into a reactor, add 1.45 kg of Raney nickel as a catalyst under nitrogen protection, then introduce hydrogen to discharge nitrogen and stabilize the pressure of the reactor at 4.1 MPa, perform a reduction reaction at 62° C. for 3.2 hours, filter, stir and mix the reaction solution with 2 times the mass of deionized water, filter again after the solid is precipitated, and dry the solid to obtain 1,4-bis(2-trifluoromethyl-4-aminophenoxy)benzene.

[0043] Step 3: Add 20.88 kg of 1,4-bis(2-trifluoromethyl-4-aminophenoxy)benzene to the reactor, then add 185 kg of acetone as a solvent and stir for 25 minutes, add 51.36 kg of toluene diisocyanate, stir and react at 62°C for 35 minutes, filter, wash the filter cake with deionized water 4 times, vacuum dry at 45°C, crush, and pass through a 200-mesh sieve to obtain a fluorinated polyurea thickener.

[0044] Step 4: Add 4.5 kg of cobalt nitrate hexahydrate, 110 kg of 2-methylimidazole, 550 L of deionized water and 2850 L of N,N-dimethylformamide into the reactor, stir at 50 ° C for 25 min and ultrasonically treat for 12 min, then add 32.5 kg of nano-iron tetroxide into the reactor, stir and react at 62 ° C for 2.5 h, cool, centrifuge, wash the precipitate with anhydrous ethanol 4 times, and dry to obtain ZIF-67 coated iron tetroxide particles.

[0045] Step 5: Disperse 16.5 kg ZIF-67 coated ferrosoferric oxide particles and 82 kg hexachlorocyclotriphosphazene with 3300 L 1,4-dioxane and add them into the reactor. Then add 82 kg 4,4'-diaminodiphenyl ether, stir at 82 ° C for 22 hours, cool, centrifuge, wash the precipitate with anhydrous ethanol 4 times, and dry to obtain flame retardant magnetic particles.

[0046] Step six: add 80kg of poly-α-olefin with a number average molecular weight of 3000 into the reactor, add 15kg of thickener into the reactor at 70℃ and a stirring speed of 350r / min, continue stirring for 35min after the thickener is added, then heat up to 170℃, add 1.7kg of polyisobutylene with a number average molecular weight of 1800, 1.2kg of calcium stearate and 0.8kg of 2,6-di-tert-butyl-p-cresol and stir for 35min, cool to 90℃, add flame-retardant magnetic particles and continue stirring for 25min, cool to obtain high-speed and low-temperature bearing grease.

[0047] Example 3

[0048] This embodiment provides a high-speed low-temperature bearing grease, including the following implementation steps:

[0049] Step 1: Mix choline chloride and urea in a mass ratio of 1:1, stir for 60 minutes at 125°C and 500r / min, and cool to obtain an ionic liquid; add kg of ionic liquid into a reactor, then add 90kg of 2-chloro-5-nitrotrifluorotoluene and 22kg of hydroquinone into the reactor, stir and react for 4 hours at 90°C, stir and mix the reaction product with the same mass of deionized water, then add ethyl acetate with an equal volume of deionized water and stir for 30 minutes, stand and extract, collect the organic phase and remove the ethyl acetate by rotary evaporation, recrystallize with anhydrous ethanol, complete the product purification, and obtain 1,4-bis(2-trifluoromethyl-4-nitrophenoxy)benzene.

[0050] Step 2: Add 25 kg of 1,4-bis(2-trifluoromethyl-4-nitrophenoxy)benzene and 200 kg of anhydrous ethanol into a reactor, add 1.5 kg of Raney nickel as a catalyst under nitrogen protection, then introduce hydrogen to discharge nitrogen and stabilize the pressure of the reactor at 4.2 MPa, perform a reduction reaction at 65° C. for 3.5 hours, filter, stir and mix the reaction solution with 2 times the mass of deionized water, filter again after the solid is precipitated, and dry the solid to obtain 1,4-bis(2-trifluoromethyl-4-aminophenoxy)benzene.

[0051] Step 3: Add 20.88 kg of 1,4-bis(2-trifluoromethyl-4-aminophenoxy)benzene to the reactor, then add 192 kg of acetone as a solvent and stir for 30 minutes, add 51.36 kg of toluene diisocyanate, stir and react at 70°C for 40 minutes, filter, wash the filter cake with deionized water 5 times, vacuum dry at 50°C, crush, and pass through a 200-mesh sieve to obtain a fluorinated polyurea thickener.

[0052] Step 4: Add 5 kg of cobalt nitrate hexahydrate, 120 kg of 2-methylimidazole, 600 L of deionized water and 3000 L of N,N-dimethylformamide into the reactor, stir at 60 ° C for 30 min and ultrasonically treat for 15 min, then add 35 kg of nano-iron tetroxide into the reactor, stir and react at 65 ° C for 3 h, cool, centrifuge, wash the precipitate with anhydrous ethanol 5 times, and dry to obtain ZIF-67 coated iron tetroxide particles.

[0053] Step 5: Disperse 18 kg of ZIF-67 coated ferrosoferric oxide particles and 90 kg of hexachlorocyclotriphosphazene with 3600 L of 1,4-dioxane and add them into the reactor. Then add 90 kg of 4,4'-diaminodiphenyl ether, stir at 85 ° C for 24 hours, cool, centrifuge, wash the precipitate with anhydrous ethanol for 5 times, and dry to obtain flame-retardant magnetic particles.

[0054] Step six: add 85kg of poly-α-olefin with a number average molecular weight of 4000 into the reactor, add 18kg of thickener into the reactor at 80°C and a stirring speed of 500r / min, continue stirring for 40min after the thickener is added, then heat up to 180°C, add 2.5kg of polyisobutylene with a number average molecular weight of 2000, 2kg of sodium stearate zinc stearate and 1kg of 2,6-di-tert-butyl-p-cresol and stir for 40min, cool to 100°C, add flame-retardant magnetic particles and continue stirring for 30min, cool to obtain high-speed and low-temperature bearing grease.

[0055] Comparative Example 1: Based on Example 3, the thickener was replaced with commercially available hydroxyaluminum distearate, and the other steps remained unchanged to prepare a high-speed and low-temperature bearing grease.

[0056] Comparative Example 2: Based on Example 3, no flame-retardant magnetic particles were added, and the other steps remained unchanged to prepare a high-speed and low-temperature bearing grease.

[0057] Comparative Example 3: Based on Example 3, 90 kg of hexachlorocyclotriphosphazene was dispersed with 3600 L of 1,4-dioxane and added to the reactor, and then 90 kg of 4,4'-diaminodiphenyl ether was added to react to prepare a flame retardant, and the flame retardant was used to replace the magnetic flame retardant particles. The other steps remained unchanged to prepare a high-speed and low-temperature bearing grease.

[0058] Performance tests were performed on Examples 1 to 3 and Comparative Examples 1 to 3, and a water spray performance test was performed with reference to SH / T01019. 4 g of different high-speed and low-temperature bearing greases were added to a 204 type ball bearing, which was rotated at a speed of 600 r / min. The water temperature was controlled to be 38°C and sprayed on the protective plate of the bearing sleeve at a flow rate of 5 mL / s. The water spray resistance of the high-speed and low-temperature bearing grease was evaluated by the weight percentage of grease washed away by water within 1 hour. Different high-speed and low-temperature greases were applied on a glass sheet and immersed in 90°C distilled water for 3 hours. , according to DIN51807, the water resistance of grease was judged (including 1a-3, 1a: no change, 1b: grease surface discoloration, 2: grease dissolves and distilled water becomes turbid, 3: grease further dissolves and distilled water becomes milky white emulsion); according to ASTMD3801, the flame retardancy of different high-speed and low-temperature bearing greases was tested, and 1mm thick different greases were applied on both sides of a 13mm×127mm metal mesh, and then burned at the bottom with burning methane gas, removed after 10s and observed the burning situation, and evaluated its flame retardancy. The results are shown in Table 1:

[0059] Table 1

[0060]

[0061] It can be seen from Table 1 that the high-speed and low-temperature bearing grease in Examples 1 to 3 has excellent water resistance and flame retardancy after adding the homemade thickener. Comparative Examples 2 and 3 show that the magnetic flame retardant particles help to increase the water resistance and flame retardancy because the magnetic particles help to increase the stability of the high-speed and low-temperature grease.

[0062] It should be noted that, in this article, terms such as "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0063] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. High-speed and low-temperature bearing grease, characterized in that: The following raw materials are included by mass: Base oil 75-85 parts, thickener 12-18 parts, flame retardant magnetic particles 8-12 parts, tackifier 1-2.5 parts, structural stabilizer 0.5-2 parts, antioxidant 0.5-1 parts; The thickener is prepared by the following steps: Step 1: Add 1,4-bis(2-trifluoromethyl-4-nitrophenoxy)benzene and anhydrous ethanol into a reactor, add Raney nickel under nitrogen protection, introduce hydrogen to stabilize the pressure of the reactor at 4-4.2 MPa, carry out reduction reaction at 60-65°C for 3-3.5 hours, filter, stir with deionized water to precipitate solid, filter, and dry to obtain 1,4-bis(2-trifluoromethyl-4-aminophenoxy)benzene; Step 2: Add 1,4-bis(2-trifluoromethyl-4-aminophenoxy)benzene and acetone into a reaction kettle, stir for 20-30 minutes, then add toluene diisocyanate, stir and react at 55-70°C for 30-40 minutes, filter, wash the filter cake with deionized water for 3-5 times, vacuum dry at 40-50°C, crush, and pass through a 200-mesh sieve to obtain a fluorinated polyurea thickener; The usage ratio of 1,4-bis(2-trifluoromethyl-4-aminophenoxy)benzene, acetone and toluene diisocyanate is 17.4g:150-160g:42.8g; The base oil is a poly-alpha-olefin with a number average molecular weight of 2000-4000; The tackifier is polyisobutylene with a number average molecular weight of 1500-2000; The structural stabilizer is any one of sodium stearate, calcium stearate and zinc stearate; The flame retardant magnetic particles are prepared by the following steps: Step 1: add cobalt nitrate hexahydrate, 2-methylimidazole, deionized water and N,N-dimethylformamide into a reaction kettle, stir at 40-60°C for 20-30min and ultrasonically treat for 10-15min, add nano-ferroferric oxide, stir at 60-65°C for 2-3h, cool, centrifuge, wash and dry to obtain ZIF-67 coated ferroferric oxide particles; the dosage ratio of cobalt nitrate hexahydrate, 2-methylimidazole, deionized water, N,N-dimethylformamide and nano-ferroferric oxide is 0.4-0.5g:10-12g:50-60mL:270-300mL:3-3.5g; Step 2: Disperse the ZIF-67-coated ferroferric oxide particles and hexachlorocyclotriphosphazene with 1,4-dioxane and add them into a reactor, then add 4,4'-diaminodiphenyl ether, stir at 80-85°C for 20-24h, cool, centrifuge, wash, and dry to obtain flame-retardant magnetic particles; the dosage ratio of the ZIF-67-coated ferroferric oxide particles, hexachlorocyclotriphosphazene, 1,4-dioxane and 4,4'-diaminodiphenyl ether is 0.5-0.6g:2.5-3g:100-120mL:2.5-3g.

2. The high-speed and low-temperature bearing grease according to claim 1, characterized in that: The 1,4-bis(2-trifluoromethyl-4-nitrophenoxy)benzene is prepared by the following steps: Choline chloride and urea are mixed in a mass ratio of 1:1, stirred at 120-125°C and 200-500r / min for 40-60min, and cooled to obtain an ionic liquid; the ionic liquid, 2-chloro-5-nitrotrifluorotoluene and hydroquinone are stirred and reacted at 80-90°C for 3-4h, the reaction product is mixed with deionized water and ethyl acetate, and the mixture is allowed to stand for extraction, the organic phase is collected and then rotary evaporated, and recrystallized with anhydrous ethanol to obtain 1,4-bis(2-trifluoromethyl-4-nitrophenoxy)benzene.

3. The high-speed and low-temperature bearing grease according to claim 2, characterized in that: The usage ratio of the ionic liquid, 2-chloro-5-nitrotrifluorotoluene and hydroquinone is 2.8-3g:45g:11g.

4. The high-speed and low-temperature bearing grease according to claim 1, characterized in that: The usage ratio of 1,4-bis(2-trifluoromethyl-4-nitrophenoxy)benzene, anhydrous ethanol and Raney nickel is 2.4-2.5g:20g:0.14-0.15g.

5. The high-speed and low-temperature bearing grease according to claim 1, characterized in that: The antioxidant is any one of 2,6-di-tert-butyl-4-methylphenol and 2,6-di-tert-butyl-p-cresol.

6. The method for preparing high-speed low-temperature bearing grease according to claim 1, characterized in that: The steps include: Add the base oil into the reactor, add the thickener into the reactor and continue stirring for 30-40 minutes at 60-80°C and a stirring speed of 200-500r / min, raise the temperature to 160-180°C, add the viscosity enhancer, structural stabilizer and antioxidant and stir for 30-40 minutes, cool down to 80-100°C, add flame-retardant magnetic particles and continue stirring for 20-30 minutes, cool to obtain bearing grease.

Citation Information

Patent Citations

  • High-performance lubricating grease and preparation method thereof

    CN109868177A

  • Use of a lubricating fat composition comprising base oil, thickeners and / or fixed lubricant, preservative and additives, as a lubricant in brewery plants

    DE102005013266A1